Pengaruh Ukuran Perusahaan, Arus Kas Operasional, Dan Net Profit Margin (Npm) Terhadap Return Saham - Stepanus, David; Ratih, Suklimah (Jurnal Syntax Fusion, 2021)
Return is a result obtained from an investment. In the research needed for investors to invest in order to minimize losses from investing, there are several factors that affect the size of the returns in the company. From the company as well as from external companies. Therefore this study aims to see the effect of Company Size, Operational Cash Flow, and Net Profit Margin (NPM) on Stock Returns in Automotive companies in 2015-2019.The sampling method in this study used purposive sampling so that the researchers found 11 companies that match the criteria in 2015-2019, so that the research analyzed was 55 samples. The testing technique in this research is in the form of classical assumption test, multiple linear regression analysis, coefficient determination test, and T test.The results showed that company size, operating cash flow and net profit margin did not have a significant effect on stock returns.